Is Irrigation Rehabilitation Good for Poor Farmers? An Impact Evaluation of a Non-experimental Irrigation Project in Peru - Del Carpio, Ximena V. (2012)
This paper analyses the effect of a set of irrigation rehabilitation projects conducted over the last 10 years in Peru. The projects were conducted without the aim or the tools for a full-fledged impact evaluation. Nevertheless, this paper attempts an evaluation through the use of alternative data sources such as household surveys and geographic information, a strategy of identification of beneficiaries and control households based on spatial proximity to the projects' sites, and an econometric approach consisting of a double-differencing technique. The empirical analysis is guided and interpreted with the help of a theoretical model that considers the effects of an irrigation project on the distribution of production, employment and income for different types of landowners. The paper concludes that the irrigation projects implemented in Peru had a positive impact on intended beneficiary households, but not in the way it could have been simplistically expected. The project did benefit the poor but not by increasing production in their own small plots but by providing them with better employment opportunities in larger farms.